Effectiveness of platelet rich plasma in pain management of osteoarthritis knee: double blind, randomized comparative study - Ghai,Babita (2019)
Abstract Background: Intra-articular injections of platelet-rich plasma to treat symptoms of knee osteoarthritis have been successfully used in young patients. However in most of these studies the control and test knees were present in different patients thus incorporating a large amount of bias in the results. Therefore, the present study was designed in which patients with bilateral osteoarthritis knee were included and platelet-rich plasma was administered in one knee and normal saline in another knee of same patient. Methods: 20 patients aged 30–65 years with bilateral osteoarthritis knees (ASA class I and II) of either gender were included in the study. Patients were randomized to receive platelet-rich plasma and normal saline in one of the two knees. The primary outcome was VAS and WOMAC score at 6 months after procedure. The secondary outcome included changes in joint stiffness, physical function, any adverse effects noted during the course of study. Results: The baseline VAS score in platelet-rich plasma knee was 8.4 ± 0.88 which improved significantly to 4.85 ± 2.48 (p < 0.001) at 6 months as compared to normal saline knee (p = 0.017). The WOMAC pain score also improved from baseline (14.5 ± 1.3) to over 6 month 7.00 ± 4.24 (p < 0.001) in platelet-rich plasma knee while in the normal saline knee, no significant change occurred from baseline to six months (10.2 ± 1.2 to 10.05 ± 1.23). There was also significant decrease in stiffness and improvement of physical activity in the platelet-rich plasma knee as compared to normal saline knee. Conclusion: The present study showed significant decrease in pain and stiffness and improvement of physical functions of knee joint with intra-articular platelet-rich plasma injection as compared to normal saline.